Burden of comorbid anxiety and depression in patients with inflammatory bowel disease: a systematic literature review. (2nd September 2021) - Dubinsky, Marla C.; Dotan, Iris; Rubin, David T.; Bernauer, Mark; Patel, Dipen; Cheung, Raymond; Modesto, Irene; Latymer, Mark; Keefer, Laurie
ABSTRACT: Introduction: Patients with inflammatory bowel disease (IBD), including Crohn's disease and ulcerative colitis, often have comorbid anxiety and depression that affects their quality of life (QoL) and management of their IBD. Areas covered: A systematic literature review (SLR) was conducted to identify articles and conference abstracts on comorbid anxiety and depression in IBD patients using MEDLINE® and Embase® (January 2003 − June 2018). The impact of these psychological comorbidities on QoL and economic burden was examined. Non-pharmacologic interventions and disease-specific unmet clinical needs associated with these comorbidities were also evaluated. Expert opinion: There is evidence that individual and group-based cognitive behavioral therapy can reduce rates of anxiety and depression in adults and adolescents with IBD. Patients with IBD and anxiety or depression had an increased risk of hospitalization, emergency department visits, readmission, and used outpatient services more often than people without these conditions. Several disease-specific unmet clinical needs for IBD patients were identified. These included lack of reimbursement for mental-health care, inconsistent screening for psychological comorbidities and patients not consulting mental-health professionals when needed. IBD patients may benefit from integrated medical and psychological treatment, and should be considered for behavioral treatment. Plain Language Summary Background: People with IBD may have mental-health conditions, such as anxiety and depression. These conditions can affect people's quality of life and how they manage their IBD. What did this review look at?: We found 79 publications on anxiety or depression in people with IBD, published between January 2003 and June 2018. In people with IBD and anxiety or depression, researchers looked at: the impact on health-related quality of life and healthcare utilization, including access to and reimbursement for mental-health services how effective interventions that do not involve the use of medicines were (known as non-pharmacologic therapy). What were the main findings from this review?: People with IBD and anxiety or depression were more likely to be admitted to hospital and visit emergency departments than people without these conditions. Access to mental-health care varied and some people with IBD were not screened for depression. Individual and group-based talking therapy (known as cognitive behavioral therapy) reduced rates of anxiety and depression in some people with IBD. What were the main conclusions from this review?: We found evidence that people with IBD and anxiety or depression may benefit from certain non-pharmacologic interventions. However, many people with IBD and anxiety or depression did not have access to mental-health services. Healthcare professionals should address gaps in patient care to improve outcomes in people with IBD and anxiety or depression. See Additional file 1 for an infographic plain language summary.